Science, demons, and gods in the battle against the COVID‐19 epidemic. (27th July 2020) - Bretelle‐Establet, Florence
Abstract: This spotlight article reflects on President Xi Jinping's handling of the COVID‐19 epidemic and evaluates its specificities by making a brief incursion into the history of Chinese official responses to epidemics. This analysis shows that Xi Jinping's response to the COVID‐19 epidemic differs from official responses to the 2003 SARS epidemic and the cerebrospinal meningitis epidemic of 1966–1967, and is used to assert his legitimacy on both the local and the international stage. By sharing data, even if it was not as accurate as claimed, Xi Jinping has presented himself as a trustworthy international partner, leading a country that is at the forefront of scientific research, capable of vigorously implementing epidemic preparedness measures, and destined to become a major player in global health. On the Chinese stage, he showed that the central government has regained control over local public health organizations and that public health is once again a key government priority. As part of his response, Xi Jinping also honored gods of the Chinese pantheon, in a seeming contradiction with communism and science. I argue that, by combining the most advanced technology with a religious heritage, Xi Jinping is skillfully creating an image of himself not only as powerful and modern, but also as a leader undeniably rooted in Chinese tradition.